Gusto ko nang lumaki! I want to be all grown up! - Malabed, Liwliwa; Agsaway, Domz; Bravo, Becky (Quezon City Lampara Publishing House, Inc., 2013)
"Buding is the youngest child. She is annoyed by her elder siblings. She is always being ordered around by them, and threatened by them a monster will seize her. One time, she is persuaded to trade her ice cream for a doll that transforms into a string bean. But her brothers have all but finished everything, including the cone, and still there is no doll. Buding really wants to be all grown up..."
Stories with moral values
Text in Filipino and English.
The Philippine Board on Books for Young People-Salanga prize honorable mention 2005.